Efficacy and safety of a CXCR2 antagonist, AZD5069, in patients with uncontrolled persistent asthma: a randomised, double-blind, placebo-controlled trial. Issue 10 (October 2016) - O'Byrne, Paul M; Metev, Hristo; Puu, Margareta; Richter, Kai; Keen, Christina; Uddin, Mohib; Larsson, Bengt; Cullberg, Marie; Nair, Parameswaran
Summary: Background: Airway neutrophilic inflammation is a pathological feature in some patients with severe asthma. Stimulation of the chemokine receptor CXCR2 mediates neutrophil migration into the airways. We investigated the safety and efficacy of AZD5069, a CXCR2 antagonist, as an add-on therapy in patients with uncontrolled severe asthma. Methods: In this multicentre, randomised, double-blind, placebo-controlled, dose-finding trial, we enrolled patients aged 18 years or older with uncontrolled asthma despite combination therapy with long-acting β2 agonists and medium-dose or high-dose inhaled corticosteroids. Patients were randomised in a 1:1:1:1 ratio via an interactive voice-response or web-response system to receive 5, 15, or 45 mg oral AZD5069 twice daily or matched placebo. The primary endpoint was the number of severe asthma exacerbations in 6 months. Safety was assessed in the 6-month treatment period and an optional 6-month safety extension. This trial is registered withClinicalTrials.gov, numberNCT01704495 . Findings: 640 patients with a mean age of 52 (SD 11·8) years were randomised, 478 to receive AZD5069 (5 mg n=160, 15 mg n=156, and 45 mg n=162) and 162 placebo. No dose of AZD5069 reduced the rate of severe exacerbations compared with placebo (rate ratio for 5 mg 1·29, 90% CI 0·79–2·11; for 15 mg 1·53, 0·95–2·46; and for 45 mg 1·56, 0·98–2·49). Treatment with AZD5069 was generally well tolerated. The most commonly reported adverse event overall was nasopharyngitis, seen in 18 (11·5%) receiving 5 mg, 13 (8·5%) receiving 15 mg, and 18 (11·2%) receiving 45 mg AZD5069, and 31 (19·5%) of those receiving placebo. Interpretation: Treatment with this selective CXCR2 antagonist did not reduce the frequency of severe exacerbations in patients with uncontrolled severe asthma. These findings bring into question the role of CXCR2-mediated neutrophil recruitment in the pathobiology of exacerbations in severe refractory asthma. Funding: AstraZeneca.